Photosensitivity in antimony based glasses - Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, SJL; Poulain, M.; Briois, V (Natl Inst Optoelectronics, 2001)
New glass forming systems based on Sb2O3-SbPO4 has been explored. These glasses present higher thermal stability against devitrification and higher refractive index than chalcogenide glasses. Under irradiation, using Ar-laser 350nm wavelength and 50 mW power density, change on the coloration is observed. Structural and electronic modifications around Sb cations induced by such treatment have been characterized by XANES measurements at the L-Sb edges. on the one hand, XANES spectra, at the LJ edge, show a decrease of the coordination number for Sb atoms induced by exposure to light indicating a breaking of Sb-O bonds in the glassy network. on the other hand, XANES spectra, at the Lt edge, suggest a change in the oxidation state of Sb atoms. These modifications associated to the photodarkening of the glass is reversible either after a couple of days or after heating the glass at the glass transition temperature, T-g.
Keywords: antimony based glass; photosensitivity; XANES method